A case report of an early neonatal death accompanied by disseminated intravascular coagulation caused by severe acute respiratory syndrome Coronavirus-2 infection - Mitić Gorana P.; Spasić Igor G.; Panjković Milana D.; Vučković Biljana A. (Hospital Pharmacology)
Introduction: Women with coronavirus disease 2019 (COVID-19) during pregnancy are more likely to develop a severe form of the disease and have unfavorable pregnancy outcomes. Case report: We report the case of a 21-year-old woman diagnosed with disseminated intravascular coagulation (DIC) caused by COVID-19, and subsequent early neonatal death. She was referred to the hospital at 29 gestational weeks due to progression of COVID-19 symptoms. Increased plasma thrombin and fibrinolytic activity were observed on admission , and low molecular weight heparin and antibiotic therapy were started immediately. After fully developing laboratory DIC was diagnosed, an emergency Cesarean section was performed. Upon delivery severe perinatal asphyxia was diagnosed in a neonate, manifested as atony and cardiac arrest. Despite cardiopulmonary resuscitation, the newborn passed away three hours after birth. The mother recovered in several days, she was discharged in good clinical condition. Conclusion: The presented clinical case indicates the importance of an early diagnosis of DIC in SARS-CoV-2-positive pregnant women, timely therapeutic decisions, psychological support, and long-term follow-up of physical and psychological conditions.